THE PROBLEM OF DEVELOPING DIGITAL COMPETENCE IN CYBER SECURITY OF TEACHERS OF GENERAL SECONDARY EDUCATION INSTITUTIONS - KOVALENKO, Valentyna; OSYPCHUK, Tetiana (Physical and Mathematical Education, 2024)
The article examines the problem of developing digital competence in cyber security of teachers of general secondary education institutions. Scientific publications on the digital competence development of teachers of general secondary education institutions, particularly on cyber security, were analyzed. The types of cyber security threats identified by Microsoft specialists were analyzed. Protection methods have been developed that must be used to ensure a cyber-safe educational environment in a general secondary education institution. Formulation of the problem. This study presents the problem of developing digital competence in cyber security among teachers of general secondary education institutions and determines ways to ensure a cyber-safe educational environment. Materials and methods. We used a complex of methods, including analysis, systematization, generalization of scientific sources, analysis of scientific publications of domestic and foreign scientists, and generalization of our own experience. Results. The study presents the problem of developing digital competence in cyber security of teachers of general secondary education institutions and forms protection methods that must be used to ensure a cyber-safe educational environment of a general secondary education institution: authentication and authorization, data encryption, network protection and protection against malicious programs, awareness of network users, provision of data backup, monitoring and detection of unusual activity, regular software updates, development and implementation of security policies. Conclusions. Increasing the level of cyber security digital competence of teachers of general secondary education institutions is necessary. Teachers are expected to participate in lectures, seminars, webinars, round tables, and other events, as well as through cooperation with leading experts in the field of cyber security. Those activities will contribute not only to the professional growth of teachers but also provide an opportunity to give students, as well as their parents or guardians, the necessary knowledge, skills, and abilities in the field of cyber security principles in the virtual space.